2004
DOI: 10.1590/s1516-93322004000400010
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de ácidos graxos, composição centesimal e valor calórico de moluscos crus e cozidos com leite de coco da cidade de Maceió-Al

Abstract: Este estudo teve como objetivo caracterizar o perfil de ácidos graxos, a composição centesimal e o valor calórico de moluscos crus e cozidos da cidade de Maceió. Analisaram-se três espécies: sururu (Mytella falcata), maçunim (Anomalocardia brasiliana) e unha de velho (Tagelus plebeus), nas formas cruas e cozidas (ao molho de coco). Os moluscos in natura apresentaram elevados teores de umidade e proteínas. Os maiores teores de lipídeos e cinzas foram encontrados no sururu e maçunim, respectivamente. O sururu ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
3
13
0
2
Order By: Relevance
“…In all species studied, this ratio was higher than 0.45. In the mussel, the PUFAs/SFAs ratio was 0.63, which was close to the values described in three mollusc species (0.61 on average) studied by Lira et al (2004). The pink shrimp and Pacific white shrimp presented a PUFAs/SFAs ratio of 1.39 and 1.06, respectively, in line with the advice provided by the Departament of Health and Social Security (1994).…”
Section: Nutritional Quality Of the Lipid Fractionsupporting
confidence: 86%
See 1 more Smart Citation
“…In all species studied, this ratio was higher than 0.45. In the mussel, the PUFAs/SFAs ratio was 0.63, which was close to the values described in three mollusc species (0.61 on average) studied by Lira et al (2004). The pink shrimp and Pacific white shrimp presented a PUFAs/SFAs ratio of 1.39 and 1.06, respectively, in line with the advice provided by the Departament of Health and Social Security (1994).…”
Section: Nutritional Quality Of the Lipid Fractionsupporting
confidence: 86%
“…Moreover, according to the Agência Nacional de Vigilância Sanitária (ANVISA, 2012), the values of EPA + DHA obtained (328.19 mg 100 g -1 ) indicate that this species has a high omega-3 content (> 80 mg 100 g -1 ). Lira et al (2004) studied various mollusc species from the Northeast coast of Maceió in Alagoas, Brazil. These authors reported that the predominant fatty acids in Mytella falcata mussel and stout razor clam (Tagelus plebeius) were palmitic (16:0), palmitolenic (16:2n7), oleic (18:1n9), DHA (22:6n3) and EPA (20:5n3).…”
Section: Centesimal Compositionmentioning
confidence: 99%
“…There is also evidence that these fatty acids protect against aging. They are essential for the proper functioning of the eyes, membrane and PL maintenance, and development of the brain and central nervous system [3].…”
Section: Introductionmentioning
confidence: 99%
“…"Maçunim" corresponds to Anomalocardia brasiliana (Araujo, 2004;Lira et al, 2004;Boehs et al, 2008). However, according to IBAMA (2007), "maçunim" represents Tivela mactroides and this should be corrected.…”
Section: Commercial Fisheries Mollusksmentioning
confidence: 99%